CHIPPIPARAI BREED OF DOGS IN TAMIL NADU: AN ASSESSMENT OF PHYSICAL AND PERFORMANCE CHARACTERISTICS - Karthikeyan, SMK; Varumurugan, T; Hisham, A; Sivasalem, SN (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The Chippiparai dog, a unique medium-sized, sight-hound breed seen in south India, is studied to assess the distribution and breed characteristics. The breeding tract of this dog is Tirunelveli district of southern Tamil Nadu. The trademark features are fawn coat, black nostrils, black eyes, broad chest and tucked up abdomen. The overall means of body length, head length, muzzle length, tail length, height at withers, height at rump, chest girth, belly girth, ear length and ear width in adults were 60.90 ± 1.34, 21 ± 0.39, 9.56 ± 0.17, 40.28 ± 0.77, 59.56 ± 1.30, 59.84 ± 1.38, 60.36 ± 1.36, 39.30 ± 0.75, 10.92 ± 0.23 and 8.10 ± 0.18 cm respectively. Sex had significant effect (P< 0.05) on body length, and highly significant effect (P< 0.01) on height at withers and chest girth. This study shows that Chippiparai dog breed is a medium-sized indigenous sight hound dog of Tamil Nadu
Keywords: Chippiparai dog; distribution; morphology; morphometry; performance characteristics